2020
DOI: 10.1055/s-0040-1709111
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fine Needle Aspiration Cytology in the Diagnosis of Parotid Gland Tumors: Analysis of 193 Cases

Abstract: Introduction Parotid gland tumors include a wide variety of inflammatory and neoplastic diseases. The majority of these tumors are benign (80%), which usually require superficial parotidectomy, while the incidence of malignant tumors is lower (20%), requiring more radical surgery with or without neck dissection. The diagnosis cannot be established on the basis of clinical history and simple physical examination and requires complementary diagnostic methods. Fine needle aspiration cytology (FNAC) guided by ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
7
0
3
Order By: Relevance
“…In a review of the literature of the last decade, the sensitivity was reported to range between 60% and 92% and the specificity was reported to range between 87.7% and 100% [ 14 ]. Another survey showed sensitivity of 88.9%, specificity of 97.9%, positive predictive value of 93%, and negative predictive value of 96.7% and diagnostic accuracy of 95.8% [ 15 ]. Other previous studies reported sensitivity 68.96%, specificity 89.63%, positive predictive value 54.05% and negative predictive value 94.23% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the literature of the last decade, the sensitivity was reported to range between 60% and 92% and the specificity was reported to range between 87.7% and 100% [ 14 ]. Another survey showed sensitivity of 88.9%, specificity of 97.9%, positive predictive value of 93%, and negative predictive value of 96.7% and diagnostic accuracy of 95.8% [ 15 ]. Other previous studies reported sensitivity 68.96%, specificity 89.63%, positive predictive value 54.05% and negative predictive value 94.23% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies reported sensitivity 68.96%, specificity 89.63%, positive predictive value 54.05% and negative predictive value 94.23% [ 16 ]. Other studies reported that FNA sensitivity and specificity values can be variable in relation to different populations [ 17 , 18 ] where sensitivity varied between 38% [ 19 ] and 97% [ 16 ] and specificity varied between 81%13 and 100% [ 20 ].Furthermore, Dhanani R et al conducted fine needle aspiration cytology preoperatively and the results were compared with the final histopathology, which showed a sensitivity of 88.9%, specificity of 97.9%, positive predictive value of 93%, and negative predictive value of 96.7% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Độ chính xác Đinh Xuân Thành 2010 (4) 34 97% 100% 100% 100% Chauhan N 2019 (5) 31 81,8% 94,7% 90,0% 90,0% 90% Dhanani R 2020 (8) 193 88,9% 97,9% 93% 96,7% 95,8% Archondakis S 2021 (7) 102 Trong thực tế, u tuyến mang tai thường có triệu chứng nghèo nàn, ít gây khó chịu, bênh nhân đến khám và điều trị muộn, khối u đã lớn, ảnh hưởng nhiều đến chức năng vùng mặt như liệt mặt, khít hàm và thẫm mỹ của bệnh nhân. Việc phát hiện khối u tuyến mang tai khá dễ dàng trên lâm sàng với sự hỗ trợ của các cận lâm sàng chẩn đoán hình ảnh như siêu âm ở tất cả các bệnh nhân và một số bệnh nhân được chụp CLVT.…”
Section: Giá Trị Chẩn đOán (-)unclassified
“…Về độ nhạy, theo kết quả nghiên cứu của chúng tôi FNA có độ nhạy ở mức cao 100%; cứ 100 người bị u tuyến mang tai thì FNA phát hiện được khối u ở 100 người. Kết quả cao hơn so với các nghiên cứu của trong và ngoài nước của các tác giả Chauhan N (5) 81,8%; Dhanani R (8) 88,9% và Archondakis S (7) 82,2% và tác giả Đinh Xuân Thành (4) là 97%. Cỡ mẫu của nghiên cứu chúng tôi và các nghiên cứu khác không tương đồng nhau, sự khác nhau về tỷ lệ này có thể ảnh hưởng bởi nhiều yếu tố: kỹ thuật lấy mẫu u tuyến mang tai, kinh nghiệm đọc kết quả FNA.…”
Section: Giá Trị Chẩn đOán (-)unclassified
See 1 more Smart Citation